THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURES ON COMPANY PROFITABILITY - Maya Aresteria; Deddy Sulestiyono; Alfita Rakhmayani (Tax Accounting Applied Journal, 2023)
Companies with complex environmental consequences have an obligation to address their corporate social and environmental impacts. The heterogeneity of results makes research on the impact of companies in implementing CSR still very interesting to do, one of which is the impact on profitability that will be received by companies if companies carry out CSR well. This study examines how the impact caused by the company on its CSR activities on company profitability. From the test results of 54 companies listed on the IDX, it was found that CSR disclosures made by companies had an impact on company profitability.